Recreational tourism : demand and impacts - Ryan, Chris, 1945- (Aspects of tourism, 2003)
This discursive and evaluative text covers the nature of the demand for tourism and the implications of that demand. The second edition represents a significant updating of material that reflects early 21st century thought.